Disentangling Obstacles to Knowledge Co-Production for Early-Career Researchers in the Marine Sciences - Rölfer, Lena; Elias Ilosvay, Xochitl E.; Ferse, Sebastian C.A.; Jung, Julia; Karcher, Denis B.; Kriegl, Michael; Nijamdeen, TWGF Mafaziya; Riechers, Maraja; Walker, Elizabeth Zoe (Frontiers in Marine Science, 2022)
Knowledge co-production involving researchers and non-academic actors is becoming increasingly important for tackling sustainability issues. Coastal and marine social-ecological systems are one example where knowledge co-production is important, yet also particularly challenging due to their unique characteristics. Early-Career Researchers (ECRs) often face specific obstacles when engaging in the process of knowledge co-production. In this perspective paper, we shed light on the particular characteristics of knowledge co-production in marine social-ecological systems and the obstacles ECRs in the marine sciences face. Based on these obstacles, we discuss actions that can be taken at various organizational levels (institutional, community, supervisor, and individual) in order to leverage change towards a more inclusive environment for ECRs engaging in knowledge co-production. We conclude that both bottom-up (individual to institutions) and top-down (institutions to individual) actions are required. However, we emphasize the responsibilities of institutions to create conditions in which the needs of ECRs are met. This will be necessary to adequately support ECRs engaging in knowledge co-production and thus contribute to tackling sustainability challenges in coastal and marine social-ecological systems.